Photocatalytic degradation of cylindrospermopsin under UV-A, solar and visible light using TiO2. Mineralization and intermediate products. (January 2015) - Fotiou, Theodora; Triantis, Theodoros; Kaloudis, Triantafyllos; Hiskia, Anastasia
Abstract: Cyanobacteria (blue-green algae) are considered an important water quality problem, since several genera can produce toxins, called cyanotoxins that are harmful to human health. Cylindrospermopsin (CYN) is an alkaloid-like potent cyanotoxin that has been reported in water reservoirs and lakes worldwide. In this paper the removal of CYN from water by UV-A, solar and visible light photocatalysis was investigated. Two different commercially available TiO2 photocatalysts were used, i.e., Degussa P25 and Kronos-vlp7000. Complete degradation of CYN was achieved with both photocatalysts in 15 and 40 min under UV-A and 40 and 120 min under solar light irradiation, for Degussa P25 and Kronos vlp-7000 respectively. Experiments in the absence of photocatalysts showed that direct photolysis was negligible. Under visible light irradiation only the Kronos vlp-7000 which is a visible light activated catalyst was able to degrade CYN. A number of intermediates were identified and a complete degradation pathway is proposed, leading to the conclusion that hydroxyl radical attack is the main mechanism followed. TOC and inorganic ions (NO2 −, NO3 −, SO4 2− and NH4 + ) determinations suggested that complete mineralization of CYN was achieved under UV-A in the presence of Degussa P25.